Helminth parasites of the Newfoundland short-finned squid, Illex illecebrosus illecebrosus (LeSueur) (Cephalopoda: Decapoda) - Brown, Elizabeth L.; Threlfall, William (Canadian Journal of Zoology, 1968)
Five genera of cestode parasites were found in the short-finned squid. Representatives of three of these, Pelichnibothrium speciosum, Monticelli, Scolex polymorphus Rudolphi, and Nybelinia sp. are new host records. The other two genera are Phyllobothrium and Dinobothrium, both of which have previously been described from Illex illecebrosus illecebrosus. The specimens of Dinobothrium collected were identified to the species level, Dinobothrium plicitum Linton, for the first time. Contrary to conclusions drawn by other workers, the plerocercoids of Phyllobothrium sp. do not wander freely about the body of the squid in nature, but are restricted to the caecum. The wandering of plerocercoids referred to above is probably a function of rising temperature over the period between time of capture of the squid and time of examination.